If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10b + 5 = 76 + 5 Reorder the terms: 5 + 10b = 76 + 5 Combine like terms: 76 + 5 = 81 5 + 10b = 81 Solving 5 + 10b = 81 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10b = 81 + -5 Combine like terms: 5 + -5 = 0 0 + 10b = 81 + -5 10b = 81 + -5 Combine like terms: 81 + -5 = 76 10b = 76 Divide each side by '10'. b = 7.6 Simplifying b = 7.6
| 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 |